New insights into xanthan synergistic interactions with konjac glucomannan: A novel interaction mechanism proposal. (25th June 2016) - Abbaszadeh, A.; MacNaughtan, W.; Sworn, G.; Foster, T.J.
Highlights: A unified model of xanthan/konjac mannan interaction based on rheological and DSC data. Interactions dependent on the conformation of the xanthan chains. An understanding of the gelation mechanism. Testing of the model by varying xanthan functional group and salt content. Abstract: The interactions of xanthans containing precise acetate and pyruvate concentration with Konjac glucomannan (KGM) were studied at different sodium chloride and polymer concentrations. A new unified model of the interaction is proposed, taking into account previous models in the literature. This study suggests that the interactions occur by two distinct mechanisms dependent on xanthan conformation. These interactions are not mutually exclusive and may co-exist and hence produce complicated traces. Consequently two types of gel which melt at different temperature ranges can be formed. Depending on the xanthan helix coil transition temperature, one or both of the synergistic states may exist in the hydrocolloid blend. The proposed model has been tested rheologically and using differential scanning calorimetry by varying salt concentration and using samples containing different functional group concentrations.